2022
DOI: 10.3390/cells11050774
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Storage Pool Deficiency and Elevated Inflammatory Biomarkers Are Prevalent in Postural Orthostatic Tachycardia Syndrome

Abstract: A significant number of postural orthostatic tachycardia syndrome (POTS) patients have platelet delta granule storage pool deficiency (δ-SPD). The etiology of POTS is unknown but a number of laboratories, including ours, have reported elevations of G-protein-coupled adrenergic receptor and muscarinic acetylcholine receptor autoantibodies in POTS patients, detected by a variety of techniques, suggesting that the disorder is an autoimmune condition. Thus, it could also be considered an inflammatory disease. In a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…A link between autoinflammation and autoimmunity is represented by the mixed pattern disease ( Rodríguez et al, 2020 ). Evidence has recently shown that POTS may in fact be a mixed pattern inflammatory disease mediated by T cells ( Gunning et al, 2022 ). This was based on a study that showed a platelet delta granule storage pool deficiency in patients with POTS and GPCR autoantibodies suggesting innate system activation ( Gunning et al, 2021 ; Gunning et al, 2022 ).…”
Section: Mechanisms Of Autonomic Dysfunction By Sars-cov-2mentioning
confidence: 99%
See 1 more Smart Citation
“…A link between autoinflammation and autoimmunity is represented by the mixed pattern disease ( Rodríguez et al, 2020 ). Evidence has recently shown that POTS may in fact be a mixed pattern inflammatory disease mediated by T cells ( Gunning et al, 2022 ). This was based on a study that showed a platelet delta granule storage pool deficiency in patients with POTS and GPCR autoantibodies suggesting innate system activation ( Gunning et al, 2021 ; Gunning et al, 2022 ).…”
Section: Mechanisms Of Autonomic Dysfunction By Sars-cov-2mentioning
confidence: 99%
“…Evidence has recently shown that POTS may in fact be a mixed pattern inflammatory disease mediated by T cells ( Gunning et al, 2022 ). This was based on a study that showed a platelet delta granule storage pool deficiency in patients with POTS and GPCR autoantibodies suggesting innate system activation ( Gunning et al, 2021 ; Gunning et al, 2022 ). It remains to be investigated whether the innate and adaptive immune systems contribute to autoantibody production against adrenergic and cholinergic receptors following SARS-CoV-2 infection.…”
Section: Mechanisms Of Autonomic Dysfunction By Sars-cov-2mentioning
confidence: 99%
“…The ill-defined grey bodies represent the α-granules, approximately 50–80/platelet. The opaque round bodies are the dense granules, ranging from 0–30/platelet, and grey string-like bodies are lysosomes [ 24 ]. Thin lines signify platelet cell membranes.…”
Section: Figurementioning
confidence: 99%
“…The mechanism of POTS is unknown, although research is continuing to find the most likely reasons. People with POTS have platelet storage pool shortage, according to Gunning et al [ 9 ], which is connected to symptoms including nosebleeds, dysmenorrhea, easy bruising, and anemia. It was also shown that persons with POTS have higher inflammatory biomarkers, all of which might indicate a chronic inflammatory condition.…”
mentioning
confidence: 99%
“…It was also shown that persons with POTS have higher inflammatory biomarkers, all of which might indicate a chronic inflammatory condition. The presented conditions, especially inflammatory markers, could be associated with a cytokine storm during COVID-19 [ 9 ]. POTS affected an estimated 1–3 million persons in the United States, well before the pandemic, according to data published by the group Dysautonomia International.…”
mentioning
confidence: 99%